IMAGE PROCESS DEVICE, METHOD AND PROGRAM - TSUJI AKIKO; HAMAGUCHI SHINGO; ITO TAKAAKI; KOBAYASHI JUNICHI (2014)
PROBLEM TO BE SOLVED: To provide a highly satisfactory image for a user.SOLUTION: An image process device comprises: a photographing image acquisition part that acquires a photographing image captured by photographing a subject as a user; a movement area setting part that sets a part of a subject area in the photographing image to a movement area in which the part thereof is caused to move in a direction toward an inner side of the subject area; and an area movement process part that moves an area set in the movement area in the direction toward the inner side of the subject area in the photographing image and outputs the photographing image in which the movement area is moved in the direction toward the inner side of the subject area. The present invention is applicable to, for example, a photographic seal preparation device capable of photographing an entire body of the subject.